The Imprint of Buddhism in Pagoda Architecture under the Ly Dynasty and Historical Values - Hong Van, Vu (International Journal of Psychosocial Rehabilitation, 2020)
Like in previous dynasties, in the Ly Dynasty Buddhism became a state religion and flourished. The thought of compassion and charity of Buddhism, which has quickly integrated into the spiritual life and has become an integral part of the daily life of Vietnamese people. According to Dai Viet Su Ky Toan Thu (1697) (the oldest history book of Vietnamese people), at that time, "a lot of people came to the pagod”a. Everyone who works also thinks of the support of the Buddha. After Ly Thuong Kiet had defeated the Song Dynasty invaders and punished the Chiem Dynasty, he had built Bao An pagoda (Thanh Hoa province today) to show his gratitude for Buddha. At the same time, Linh Nham Queen built for herself hundreds of the pagoda. When Ly Thai To ascended the king's throne, he did not build the palace, but the king built eight pagodas. The old history has depicted pagodas that were very beautiful and solemn, while the palace of the king was depicted in a modest way (Dai Viet Su Ky Toan Thu, 1697). That at the time, Buddhism architecture works had an important position and stood out even more than other architectural works. However, today to understand and know about the Ly Dynasty pagodas, we can only imagine through the foundation of the remaining architectural works and ancient archives because there are no remaining works intact; most of the works have been restored, but through it, it partly shows us the magnificent pagoda architecture under the Ly Dynasty and the influence of Buddhism in those pagodas.